Penerapan PPN Dibebaskan atas Penyerahan Barang Kena Pajak CV. ABC Melalui KKP Subhan Kristyanto - Inayah Mawar Triyanti (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Taxes are a primary source of state revenue and play a crucial role in financing national development, one of which is through Value Added Tax (VAT). In practice, the government provides tax incentives in the form of VAT waivers or exemptions to support certain sectors deemed strategic. This study aims to determine the application of VAT waivers or exemptions on the delivery of Taxable Goods (BKP) to CV. ABC through the Subhan Kristyanto Tax Consultant Office. The method used in this Final Project Report is qualitative, consisting of interviews and quantitative data in the form of figures, amounts, percentages, and calculations related to CV. ABC's tax activities, specifically regarding the application of the VAT waiver facility for the delivery of fish meal. The delivery of fish meal to CV. ABC falls under the category of BKP that is eligible for VAT waivers. In practice, the company still issues tax invoices using transaction code 08 with a VAT value of zero (Rp0). Although no VAT is collected, the transaction must still be reported in the Periodic VAT Tax Return (SPT) under the section on deliveries that are eligible for the exemption facility. Furthermore, the Input Tax related to these transactions cannot be credited and therefore becomes part of the company's expenses.
Validasi dan Finalisasi Repositori File 07 Juli 2026_Kholif Basri
Keywords: Value Added Tax; VAT is Exempt; Taxable Goods